2020
DOI: 10.3389/fphar.2020.00426
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factors in the Management of Acute Kidney Injury Following Ischemia-Reperfusion

Abstract: Ischemia-reperfusion injury (IRI), which is triggered by a transient reduction or cessation of blood flow followed by reperfusion, is a significant cause of acute kidney injury (AKI). IRI can lead to acute cell death, tissue injury, and even permanent organ dysfunction. In the clinic, IRI contributes to a higher morbidity and mortality and is associated with an unfavorable prognosis in AKI patients. Unfortunately, effective clinical drugs to protect patients against the imminent risk of renal IRI or treat alre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 94 publications
0
15
0
Order By: Relevance
“…Another gene target is fibroblast growth factor 18 (FGF18). It belongs to the FGF family that is involved in important biological and pathological processes, such as embryonic development, metabolic homeostasis and tumorigenesis through the regulation of cell differentiation, migration, proliferation and survival (Deng et al, 2020). As previously described, miR-21 was upregulated in injury with fibrosis both in mouse and human models (Chau et al, 2012).…”
Section: Discussionmentioning
confidence: 62%
“…Another gene target is fibroblast growth factor 18 (FGF18). It belongs to the FGF family that is involved in important biological and pathological processes, such as embryonic development, metabolic homeostasis and tumorigenesis through the regulation of cell differentiation, migration, proliferation and survival (Deng et al, 2020). As previously described, miR-21 was upregulated in injury with fibrosis both in mouse and human models (Chau et al, 2012).…”
Section: Discussionmentioning
confidence: 62%
“…Therefore, our present study identified tilianin as a promising therapeutic agent against I/R-induced AKI. Hypovolemia, hypotension, and heart failure are all common causes of transient ischemia, which contributed to AKI easily and explained for nearly one-third of patients requiring renal replacement therapy (Havasi and Borkan, 2011;Deng et al, 2020;Sabapathy et al, 2020). In I/R-induced AKI, proximal tubular epithelial cells were highly susceptible to injury, and apoptosis played a critical role in this process (de Ponte et al, 2021;Tonnus et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“… 40 A recent review has detailed the possible role of FGF in the management of acute renal injury following ischaemia/reperfusion (IRI). 41 Evidence suggests that alterations in the expression of endogenous FGF are associated with IRI and may alter the repair process and discovered that exogenous FGF ligand might also be protective against IRI. Mouse model studies showed that FGFR2 knockout aggravated acute tubular dysfunction.…”
Section: Discussionmentioning
confidence: 99%